Tanzania - from mining to oil and gas: Structural change or just big numbers? - Alan R. Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper extends UNU-WIDER Working Paper 2016/79, which examined the economic situation in Tanzania during the resurgence of gold and diamond production after 1999, with the situation that emerged as the country began to exploit its very large resources of natural gas mainly from the Indian Ocean. The mining boom after 1999 provided the authorities with significant lessons and opportunities associated with managing natural resource wealth. The present paper additionally examines some of the specific policy and regulatory decisions taken since 2015, and tries to assess how the multiple challenges of new natural gas wealth are being addressed. It concludes that the experience thus far is not encouraging.
Keywords: 330; Tanzania; gas; liquefied natural gas; mining; energy generation